Eksplorasi Etnomatematika Aksara Lontara dalam Pembelajaran Matematika Jenjang Sekolah Menengah Pertama - Kusumayanti, Andi; Nurul Rezky; Sudarmin; Baharuddin (FKIP Universitas Mataram, 2025)
Lontara script in ethnomathematics study can provide a deep understanding of the relationship between mathematics and local culture of the community and with the ethnomathematics approach provides opportunities for students in the culture and principles of mathematics contained in Lontara script. The purpose of this study is to explore the mathematical concepts contained in Lontara script. This type of research is qualitative with an ethnomathematics approach. Data collection techniques used are observation, interviews and documentation. Testing the validity of the data used is technical triangulation. Data analysis techniques used are data reduction, data presentation and drawing conclusions. The results of this study indicate that Lontara script has mathematical elements such as the concept of sets, geometry concepts and number concepts found in the elements of Lontara script at the Balla Lompoa Museum, Gowa Regency, South Sulawesi. In addition to mathematical aspects, Lontara script supports efforts to preserve culture in Bugis-Makassar and as a reflection of the richness of culture in Indonesia that can be linked to the concept of learning mathematics. The implications of this study are not only to enrich insight in the form of literature but also to contribute as an alternative approach to learning mathematics through the context of local culture